Efeitos do LRP6 e Frizzled6 na diferenciação endotelial de DPSC - Silva, Gleyce Oliveira [UNESP] (2015)
The aim of this study was to evaluate the function of Wnt/β-catenin signaling through LRP-6 and Frizzled-6 receptors in the differentiation of dental pulp stem cells from permanent teeth (DPSC) into endothelial cells. DPSC were transduced with EGFP-tagged lentiviral shRNA vectors (LRP6, Frizzled6 or empty vector - control) for experiments. In vitro assay evaluated GSK3-β and β-catenin expression by western blot in rhWnt1 and rhVEGF165 presence, and VEGF and CXCL-8 (IL-8) expression by ELISA. Endothelial markers expression (western blot and PCR) and tube formation were analyzed after endothelial differentiation of DPSCs. In vivo, tooth slices/scaffolds seeded with transduced DPSCs were implanted subcutaneously in back of immunodefficient mice and blood vessels were counted per immunohistochemistry for eGFP and HE staining. Active β- catenin was more expressed in shRNA-LRP6 and shRNA-Frizzled6 than in control cells, and increased with rhVEGF165 and rhWnt1 supplementation. Phosphorylated GSK3-β expression was lower, however also increased or maintained with rhVEGF165 or rhWnt1. VEGF expression was higher in shRNA-Frizzled6 than in control and shRNA-LRP6 (p<0,05), IL8 expression was lower in shRNA-LRP6, with statistically difference of the others cells. Endothelial markers CD31 and VEGFR2 expression decreased in shRNA-LRP6, but VEGFR2 expression increased in shRNAFrizzled6. shRNA-Frizzled6 and shRNA-LRP6 tube formation was lower when compared to control, however shRNA-Frizzled6 had tendency to increase proliferation in 144h. In vivo, shRNA-LRP6 showed fewer blood vessels formed than other cells (p<0,05). Collectively, the results of this study suggest that Wnt/β-catenin signaling regulates endothelial differentiation of DPSC through LRP6